THE CORRESPONDENCE OF ERASMUS: Vol. 2 (Editors: R. Mynors, D. F. Thomson, and W. K. Ferguson) - Bruneau, William A. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1977)
R. Mynors, D. F. Thomson, and W. K. Ferguson, eds. THE CORRESPONDENCE OF ERASMUS: Vol. 2. Toronto: University of Toronto Press, 1975. 25.00.